Prevalence of tuberculin reactors in mithuns (Bos frontalis) in India - Rajkhowa, S; Rajkhowa, C; Hazarika, G C (The Indian Journal of Animal Sciences, 2007)
Studies conducted on the prevalence of tuberculin reactors in 104 mithuns revealed that the percentage of tuberculin positive reactors in single intradermal comparative tuberculin test was 12. Highest prevalence (prevalence rate=19%; 95% CI=7.79-30.21) of tuberculin reactors was observed in mithuns above 6 years of age. Significant.difference was observed in the prevalence of tuberculin reactors among mithuns of different strains with the highest prevalence (prevalence rate=30%; 95% CI=12.74-47.26) recorded in Arunachal strain. No statistically significant difference was observed between male (prevalence rate=12%; 95% CI=2.07-21.93) and female (prevalence rate=11%; 95% CI=3.28- 18.72) prevalences. The prevalence was higher in farms located at the lower altitude (prevalence rate 21%; 95% CI=9.48- 32.52) than farm located at the higher altitude (prevalence rate 4%; 95% CI=0-9.1 I). Acid-fast organism was demonstrated in the smears prepared from the tuberculous lesions of four tuberculin positive reactors. This is the first study performed on mithuns from India.